The Effect of Information Asymmetry and Diversification on Company Value With Profit Management as an Intervening Variable - Desy Agustina; Etty Murwaningsari (Green Publisher Indonesia, 2025)
This empirical research aims to analyze the effect of information asymmetry and diversification on firm value with earnings management as intervening variables and profitability, firm size, and leverage as control variables. This study analyzes six research objectives in detail: a. The effect of information asymmetry on earnings management; b. The effect of diversification on earnings management; c. The effect of information asymmetry on firm value; d. The effect of diversification on firm value; e. The effect of earnings management on firm value; and f. A more significant influence between the effect of information asymmetry and the effect on firm value directly or indirectly, namely through earnings management variables. The population in this study consists of manufacturing companies listed on the Indonesia Stock Exchange, with an observation year of 2015-2019. This research uses purposive sampling. This research uses panel data regression analysis. The expected research results are: a. Information asymmetry has a negative effect on earnings management; b. Diversification has a positive effect on earnings management; c. Information asymmetry has a negative effect on firm value; d. Diversification has a negative effect on firm value, e. Earnings management has a negative effect on firm value; and f. A more significant influence between the effect of information asymmetry and the effect on firm value directly or indirectly, namely through earnings management variables